2015
DOI: 10.1002/cbdv.201400239
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes from the Roots ofOryza sativaL. and Their Inhibition Activity on NO Production in LPS‐Stimulated RAW264.7 Macrophages

Abstract: Two new pimarane diterpenoids, momilactone D (3) and momilactone E (5), along with three known diterpenoids, momilactone A (1), sandaracopimaradien-3-one (2), and oryzalexin A (4) were isolated from Oryza sativa roots. The chemical structures of the compounds were determined by spectroscopic data analysis. The isolated diterpenoids were evaluated for their ability to inhibit NO production and iNOS mRNA and protein expression in LPS-stimulated RAW264.7 macrophages. Compound 4 showed strong inhibition activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Subsequently, momilactones D ( 5 ) and E ( 6 ) were identified from the roots of O. sativa . 23 Strictly speaking, momilactone E ( 6 ), which is a 19- nor -(9 β- H)-pimarane, should have not been called ‘momilactone’ because it does not contain a lactone structure in the molecule. Two other non-lactone derivatives, 6,19 β -epoxy-3 β -hydroxy-5 α ,9 β -pimara-7,15-diene ( 7 ) 21 and (9 β- H)-pimara-7,15-diene-3 β ,6 β ,19-triol ( 8 ), 22 were subsequently isolated from the rice husks and from rice leaves after UV-irradiation, respectively.…”
Section: Natural Distribution and Chemical Classification Of (9β-h)-pmentioning
confidence: 99%
“…Subsequently, momilactones D ( 5 ) and E ( 6 ) were identified from the roots of O. sativa . 23 Strictly speaking, momilactone E ( 6 ), which is a 19- nor -(9 β- H)-pimarane, should have not been called ‘momilactone’ because it does not contain a lactone structure in the molecule. Two other non-lactone derivatives, 6,19 β -epoxy-3 β -hydroxy-5 α ,9 β -pimara-7,15-diene ( 7 ) 21 and (9 β- H)-pimara-7,15-diene-3 β ,6 β ,19-triol ( 8 ), 22 were subsequently isolated from the rice husks and from rice leaves after UV-irradiation, respectively.…”
Section: Natural Distribution and Chemical Classification Of (9β-h)-pmentioning
confidence: 99%
“…Pimarane diterpenoids with anti-inflammtory effects have been reported [ 17 , 18 ]. In our bioassay of eutypenoids A–C with several anti-inflammatory models, we found that eutypenoid B ( 2 ) had an immunosuppressive effect.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was assessed by performing an MTT assay [ 17 ]. In brief, splenocytes (4 × 10 5 cells/well) were cultured in triplicate with or without compounds 1 – 3 in a 96 well plate at 37 °C in a 5% CO 2 atmosphere for 48 h. MTT was then added to the medium (0.5 mg/mL) and incubated for 4 h before the end of the incubation period.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, momilactones A and B significantly suppressed F. oxysporum and F. solani activities in vitro [56]. Although the biological importance of momilactones and its defense role in rice and mosses have been abundantly reported in the past, it was not until recently that the molecular basis for some of these functionalities were unraveled [57][58][59][60][61]. This resulted in Momilactose (A and B) being officially patented as non-chemical herbicides a little over a decade ago, giving more credence to their value in green agriculture research [62].…”
Section: Discussionmentioning
confidence: 99%